2018
DOI: 10.1002/tl.20289
|View full text |Cite
|
Sign up to set email alerts
|

Students Engaged in Teaching

Abstract: The role of peer teaching has long been established in academia as a means to foster student engagement in the classroom, increase student learning, and as a way to reduce faculty workload. This chapter highlights the direct and powerful positive impacts of engaging students as teachers upon the student providing the instruction, those receiving it, and the institution as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…As most student pharmacists were at a stage of life in which they could closely relate to campers, positive peer-teaching and mentoring relationships occurred more naturally than they might among campers and faculty members. [15][16][17][18] These relationships led to meaningful dialogues regarding the profession and challenges faced navigating the pharmacy curriculum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As most student pharmacists were at a stage of life in which they could closely relate to campers, positive peer-teaching and mentoring relationships occurred more naturally than they might among campers and faculty members. [15][16][17][18] These relationships led to meaningful dialogues regarding the profession and challenges faced navigating the pharmacy curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14] Yet, to effectively reach high school students, it is important to engage current healthcare students as peer instructors to enhance the overall learning experience for campers. [15][16][17] Research has shown that the inclusion of peer instructors within learning is successful because of social congruence, as peers share similar social roles. Peer instructors are best able to understand the challenges of the learning experience as they have completed these same experiences in recent months or years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to near-peer mentoring, peer-teaching empowers students to teach each other and has long been a tradition in academia (Wagner, 1982;Topping, 1996) and more recently, has been used in environmental education contexts (DeVreede et al, 2014). Benefits to peer-teachers include improved communication skills, increased knowledge and understanding, enhanced problemsolving skills, and improved attitudes and confidence toward the learning environment (Benware and Deci, 1984;Galbraith and Winterbottom, 2011;Bester et al, 2017;Ford et al, 2018). These benefits are likely to extend to mentors in near-peer mentoring contexts.…”
Section: Research Mentoring and Benefits To Mentorsmentioning
confidence: 99%
“…The value of peer learning has been explored and incorporated into a variety of venues throughout higher education with integration into teaching (Ford, 2018), writing centers (Bruffee, 1984), peer tutoring and counseling (Elbulok-Charcape et al, 2019), and in academic libraries as mentors, research assistants and teaching assistants (Bodemer, 2014;Deese-Roberts and Keating, 2000;Peter, 2013;Rinto et al, 2017). At the authors' institution, multiple units outside the library have utilized peer teachers in a variety of roles including as part of orientation activities, and as mentors and tutors in courses and campus writing and math centers.…”
Section: Introductionmentioning
confidence: 99%